OCCUPATIONAL PENSIONS FUNDS: LEGAL REGULATION AND PROBLEMS - Bitinas, Audrius (Teisė, 2015)
This article analyses highlights of the occupational pension fund regulatory provisions at the European Union institutional level and in Lithuania, the organisation of the occupational pension schemes and problems. Also this article examines the relationship between the current pay-as-you-go system and the second pillar pension funds, assessing occupational pensions funds development opportunities for Lithuania. The article analyzes the advantages and disadvantages of funded pension system, evaluating occupational pensions funds system in Lithuania in line with the principle of solidarity. The author points out, that prior to the reform of the social security system and the introduction of incentives for the creation of occupational pension funds, it is necessary not only to review the legal regulation (introducing incentives for active participation in pension funds, creating alternative pension schemes, creation of the economic crisis stabilization mechanisms), but also the identification of occupational pensions funds organizational problems.